ATTITUDE TOWARDS THE EDMODO USAGE IN LEARNING ACTIVITIES FOR ENGLISH LITERATURE STUDENTS - Herland Franley Manalu; Diana Anggraeni; Asrul Munazar (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2020)
The increment of concern in the use of online learning tools into English Language Teaching to adopt the Industrial Revolution 4.0 has inspired this study to examine students’ thoughts on Edmodo, as one of the online learning tools, at the English Literature department within the University of Bangka Belitung. Edmodo is used by the researchers to discuss the students’ attitude in improving their English skills. Data were collected by means of questionnaires and interview. A Likert scale questionnaire was administered and open-ended interviews were conducted to get more information from the students. Data were qualitatively and quantitatively analysed by using SPSS v.22 Software. The results reveal that the Edmodo usage is aiding students’ cooperation in small group discussions, reflecting that teaching and learning activities established on the ground of communicative teaching method were able to improve cooperation and communication, raising students’ motivation to take part and involve in various learning and also empowering them to be self-determining and be more responsible for their own learning. This study is an endeavor to attract more researchers to do further investigations on this area within the Indonesian English learners at the university level.